Conformational plasticity of ligand-bound and ternary GPCR complexes studied by 19F NMR of the β1-adrenergic receptor - J. Niclas Frei (Nature Portfolio, 2020)
The β1-adrenergic receptor (β1AR) is a G-protein-coupled receptor (GPCRs) that binds catecholamine ligands. Here the authors employ site-specific labelling and 19F NMR measurements to characterise the structural changes and dynamics in the cytoplasmic region of β1AR upon agonist stimulation and coupling to a Gs-protein-mimetic nanobody.